Optical coherence elastography based on inverse compositional Gauss-Newton digital volume correlation with second-order shape function - Wu, Hao; Wang, Jiaqiu; Amaya Catano, Jorge Alberto; Sun, Cuiru; Li, Zhiyong (Optics express, 2022)
A digital volume correlation (DVC)-based optical coherence elastography (OCE) method with inverse compositional Gauss-Newton (IC-GN) algorithm and second-order shape function is presented in this study. The systematic measurement errors of displacement and strain from our OCE method were less than 0.2 voxel and 4 × 10 −4 , respectively. Second-order shape function could better match complex deformation and decrease speckle rigidity-induced error. Compared to conventional methods, our OCE method could track a larger strain range up to 0.095 and reduce relative error by 30-50%. This OCE method has the potential to become an effective tool in characterising mechanical properties of biological tissue.